Hubungan Pola Tidur Dengan Perkembangan Emosi Anak Usia 7 Sampai 12 Tahun Di TFK Ainul Mardhiyyah - Tumiarti; Nurul Hidayah (Intitut Agama Islam Riyadlotul Mujahidin Ngabar (IAIRM) Ponorogo, 2023)
This research discusses the relationship between sleep patterns and the emotional condition of children aged 7-12 years at TFK Ainul Mardhiyyah. This research uses descriptive qualitative methodology through a case study approach. This means that the data obtained is expressed in the form of information in the form of wording that describes the situation and conditions studied in narrative form, not in the form of numbers or statistical figures, and through an in-depth approach regarding groups, institutions, etc. over a certain period of time. Meanwhile, this research uses instruments in the form of interview techniques, observation and documentation, to reveal the facts behind the relationship between sleep patterns and the emotional conditions felt by children. In this research, children have a position as research objects who essentially have an innate soul and character like humans in general. The lifestyle that has been accustomed to in the environment where the child lives has a big influence on the child's growth and development process. However, it cannot be denied that children have different mindsets from adults. This is what then allows differences in emotional control to emerge between children and adults. This research seeks to reveal the relationship between children's sleep patterns which often influence the process of expressing their emotions. This research was conducted to help the teacher council, educational staff, and adults who are involved in children's lives, understand the habits that influence a child's emotional condition.